An analysis of the COVID-19 laboratory dataset at AiBST Laboratory in Harare, Zimbabwe, 2020 - Chipendo, Tendai; Marembo, Takudzwa; Chituri, Humphrey; Munemo, Clayton; Manangazira, Portia; Bangure, Donewell; Manasa, Justen (2022)
Introduction: coronavirus disease 2019 (COVID-19) has become a major public health problem and has spread rapidly around the globe since its first identification in Wuhan, China, in December 2019. Zimbabwe reported its first case on the 20th March 2020, and since then the disease has spread to almost every part of the country. Laboratory testing is important in controlling this pandemic. However, few studies have focused on assessing trends of SARS-CoV-2 laboratory data. We described SARS-CoV-2 data from African Institute of Biomedical Science and Technology (AiBST) Laboratory in Harare, Zimbabwe. Methods: a retrospective record review of secondary SARS-CoV-2 data from AiBST Laboratory in Harare between May to September 2020 was done. Epi Info TM 7.2.2.6 was used to generate frequencies, proportions and conduct bivariate analysis. Results: a total of 6,535 SARS-CoV-2 laboratory records were analysed. The median age of the patients was 36 years and 55% (3594/6535) were males. There was an increase in average analytical turn-around time (TAT) of SARS-CoV-2 results from May to August 2020. Analytical and preanalytical TAT remained above 2 days from August to September. Males were 1.18 times at risk of being SARS-CoV-2 infected than females (p<0.05). The risk of being SARS-CoV-2 infected increased with age from 1.06 in the 11-20 age group to 1.45 in the 41-50 age group. Conclusion: COVID-19 poses a greater threat to the older age groups and to men. The delayed TAT of SARS-CoV-2 results limits the efforts to control the pandemic. Decentralization of testing to provincial and district level would help improve result TAT.